The establishment of Central American migratory corridors and the biogeographic origins of seasonally dry tropical forests in Mexico - Willis, Charles G.; Franzone, Brian F.; Xi, Zhenxiang; Davis, Charles C. (Frontiers in Genetics, 2014)
Biogeography and community ecology can mutually illuminate the formation of a regional species pool or biome. We apply phylogenetic methods to a large and diverse plant clade, Malpighiaceae, to characterize the formation of its species pool in Mexico, and its occupancy of the seasonally dry tropical forest (SDTF) biome that occurs there. We find that the 162 species of Mexican Malpighiaceae represent 33 dispersals from South America beginning in the Eocene and continuing until the Pliocene ( 46.4 – 3.8 Myr). Furthermore, dispersal rates between South America and Mexico show a significant six-fold increase during the mid-Miocene ( 23.9 Myr). We hypothesize that this increase marked the availability of Central America as an important corridor for Neotropical plant migration. We additionally demonstrate that this high rate of dispersal contributed substantially more to the phylogenetic diversity of Malpighiaceae in Mexico than in situ diversification. Finally, we show that most lineages arrived in Mexico pre-adapted with regard to one key SDTF trait, total annual precipitation. In contrast, these lineages adapted to a second key trait, precipitation seasonality, in situ as mountain building in the region gave rise to the abiotic parameters of extant SDTF. The timing of this in situ adaptation to seasonal precipitation suggests that SDTF likely originated its modern characteristics by the late Oligocene, but was geographically more restricted until its expansion in the mid-Miocene. These results highlight the complex interplay of dispersal, adaptation, and in situ diversification in the formation of tropical biomes. Our results additionally demonstrate that these processes are not static, and their relevance can change markedly over evolutionary time. This has important implications for understanding the origin of SDTF in Mexico, but also for understanding the temporal and spatial origin of biomes and regional species pools more broadly.